2019
DOI: 10.20944/preprints201902.0215.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing Host-Plant Driven Speciation in Phytophagous Insects: A Phylogenetic Perspective

Abstract: During the last two decades, ecological speciation has been a major research theme in evolutionary biology. Ecological speciation occurs when reproductive isolation between populations evolves as a result of niche differentiation. Phytophagous insects represent model systems for the study of this evolutionary process. The host-plants on which these insects feed and often spend parts of their life cycle constitute ideal agents of divergent selection for these organisms. Adaptation to feeding on different host-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 184 publications
(185 reference statements)
0
1
0
Order By: Relevance
“…Most of the species feed on either one (monophagous) or a few related plant species (oligophagous) [28]. In general, studies have shown positive correlations between the diversity of phytophagous insects and host plants [29][30][31][32], with examples of insect speciation occurring in the absence of host plant diversification being rarer [33]. A common driver of speciation among phytophagous insects, including psyllids, is adaptation to different host plant species [28,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the species feed on either one (monophagous) or a few related plant species (oligophagous) [28]. In general, studies have shown positive correlations between the diversity of phytophagous insects and host plants [29][30][31][32], with examples of insect speciation occurring in the absence of host plant diversification being rarer [33]. A common driver of speciation among phytophagous insects, including psyllids, is adaptation to different host plant species [28,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%